Perancangan dan Implementasi Sistem Informasi Manajemen Operasional dan Penggajian Berbasis Web Menggunakan Model Waterfall - Suhadi Parman; Gina Khayatun Nufus; Sokid; Kahfi Gunardi; Muhammad Iszul Wilsa (Fakultas Teknik Universitas Hamzanwadi, 2026)
Micro, Small, and Medium Enterprises such as E-Donuts face challenges in daily operational management, sales recording, packaging and donut stock management, and employee payroll because they still rely on manual processes. This study aims to design and implement EdoBest, a web-based operational management and payroll application developed using the Waterfall model. The development process includes planning, requirement analysis through interviews and observation, UML-based system design and responsive interface design, implementation using Laravel 12 and MySQL, black-box testing, and maintenance. The novelty of EdoBest lies in the integration of culinary MSME operational modules into a single system, including delivery batch management, multi-outlet management, packaging and donut stock management, employee activity recording, cash advance management, report validation, and automatic payroll calculation based on daily operational data. The quantitative testing results show that 16 functional test scenarios, consisting of 10 Admin scenarios and 6 Employee scenarios, were successfully executed with a 100% success rate. This research contributes a functionally tested design and implementation of an integrated information system that improves recording accuracy, reporting efficiency, real-time monitoring, and decision-making support for multi-outlet culinary MSMEs.